Table of Content - - (Journal of Educational and Psychological Sciences, 2023)
Table of Content: 1. The role of business incubators in Saudi universities in supporting entrepreneurial thought in light of the knowledge economy and the requirements for its activation according to reference documents Dr. Noof Atallah Alanazi, Dr. Etaf Lahig Alanazi, Dr. Norah Obaid Alsalhani 2. The extent of social studies teachers’ familiarity with the values of integrity from the point of view of educational supervisors in Kingdom of Saudi Arabia Mr. Bandar Abdullah Mutlaq Almutlaq, Mrs. Wafa Abdullah Ali Alshehri 3. A proposed vision for developing the academic performance of Saudi universities in light of lean management Co-Prof. Elham Naief Al-Rajhi 4. The State of Electronic Data Wall Usage on E-learning platforms from the Perspectives of Middle School Female Teachers Mrs. Muslihah Rashed Alluhaybi, Mrs. Rana Atif Sobahi 5. Future Thinking among twelfth grade students in Government schools in Sultanate of Oman in Light of Some Variables Dr. Issa Khamis Ali Al-Kharusi 6. Teachers’ Perception and Attitude towards Gifted Students Focusing on Their Giftedness Characteristics in Primary Schools in Riyadh: Kingdom of Saudi Arabia Mrs. Azizh Abdullah Almatroodi